Kinerja Pramusaji Terhadap Kepuuasan Pelanggan Di Whistel SMK Wirasaba Karawang: The Emergence of ESG Mutual Funds in Indonesia: A Strategic Analysis of Retail Investors - Nur Hasanah; Rosandi Ardi Noegraha; Sri Indrayanti (Jurnal Bisnis dan Ekonomi, 2025)
This study aims to determine the effect of waiters’ performance on customer satisfaction at Whistel SMK Wirasaba Karawang. The research method used is quantitative with a descriptive correlational approach. The population in this study consisted of all customers of Whistel SMK Wirasaba Karawang, with a sample of 65 respondents determined using the total sampling technique. Data were collected through questionnaires that had been tested for validity and reliability. Data analysis was conducted using correlation tests and simple linear regression. The results showed that waiters’ performance had a positive and significant relationship with customer satisfaction. This indicates that the better the waiters’ performance in serving customers, the higher the level of satisfaction experienced by customers. The conclusion of this study is that improving the competence and service quality of waiters is an important factor in maintaining and increasing customer satisfaction at Whistel SMK Wirasaba Karawang.